The eighth root of the infinitely nested fraction, 2 2 0 7 − 2 2 0 7 − 2 2 0 7 − 2 2 0 7 − ⋱ 1 1 1 can be expressed as d a + b c , where a , b , c , d are positive integers with c square-free and d minimized.
Find a + b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
sir in the beginning of your solution the number should be 2207 and not 2027
Log in to reply
Corrected. Isn’t it more important to correct the question? You have still got this to do...
My solution is very similar to Mark's, with minor differences in terminology. I suspect that there is essentially only one (correct) way to do these kinds of problems.
Consider the iteration function f ( x ) = 2 2 0 7 − x 1 , an increasing function for positive x . We are asked to find lim n → ∞ f n ( 2 2 0 7 ) , if this limit does indeed exist. Solving the quadratic equation f ( x ) = x produces two fixed points, the larger one being a = 2 1 ( 2 2 0 7 + 9 8 7 5 ) < 2 2 0 7 . Note that f ( x ) > f ( a ) = a for x > a since f is increasing; thus f n ( 2 2 0 7 ) > a for all n . Now f ( x ) < x for x > a (consider x = 2 2 0 7 as a sample point). Thus f n ( 2 2 0 7 ) is a decreasing sequence, bounded by a , and as such it has a limit. Since this limit is a fixed point of f , by continuity, we can conclude that lim n → ∞ f n ( 2 2 0 7 ) = a .
As Mark lucidly explains, 8 a = 2 1 ( 3 + 5 ) , and the answer is 1 1 .
Problem Loading...
Note Loading...
Set Loading...
We are being asked to calculate the eight root of the continued fraction β = 8 2 2 0 7 − 2 2 0 7 − 2 2 0 7 − 2 2 0 7 − ⋯ 1 1 1 Consider the sequence a n = 2 2 0 7 − a n − 1 1 with a 0 = 2 2 0 7 , and let α be the larger root of the equation x 2 − 2 2 0 7 x + 1 = 0 namely α = 2 1 ( 2 2 0 7 + 9 8 7 5 ) Note that α < a 0 ≤ 2 2 0 7 . Thus 2 2 0 7 > 2 2 0 7 − a 0 − 1 > 2 2 0 7 − α − 1 = α and hence α < a 1 < a 0 ≤ 2 2 0 7 . If n ∈ N and α < a n < a n − 1 ≤ 2 2 0 7 then a n + 1 = 2 2 0 7 − a n − 1 > 2 2 0 7 − α − 1 = α while a n − a n + 1 = a n − 1 − a n − 1 − 1 = a n a n − 1 a n − 1 − a n > 0 so that α < a n + 1 < a n ≤ 2 2 0 7 . Hence, by induction, we have shown that ( a n ) is a monotonic decreasing sequence with a n > α for all n , and hence ( a n ) converges to some limit a ≥ α . Since a n + 1 a n − 2 2 0 7 a n + 1 = 0 for all n , we deduce that a 2 − 2 2 0 7 a + 1 = 0 . From this we deduce that a = α . Thus the continued fraction is equal to α = 2 1 ( 2 2 0 7 + 9 8 7 5 ) , and we need to calculate the eighth root β = 8 α of α .
Now 4 4 1 4 = 4 7 2 + 5 × 2 1 2 and 9 8 7 = 2 1 × 4 7 , and hence α = 2 1 ( 4 7 + 2 1 5 ) . Since 9 4 = 7 2 + 5 × 3 2 and 2 1 = 7 × 3 we see that 4 α = 2 1 ( 7 + 3 5 ) . Finally we see that β = 8 α = 2 1 ( 3 + 5 ) , making the answer 3 + 1 + 5 + 2 = 1 1